Development of Blended Learning-Oriented Worksheets to Train Students Metacognitive Skills on The Rate of Reaction Material - Mustafidah, Eka Hidayatul; Azizah, Utiya (Jurnal Pendidikan MIPA, 2022)
During the Covid-19 pandemic, blended learning became one of the innovations in learning. This study aims to develop blended learning-oriented worksheets to train students' metacognitive skills on the rate of reaction material. This research method uses the ADDIE model. The instruments used are validation sheets, pre-test and post-test sheets of metacognitive skills, student response questionnaire, student activity observation sheets, and metacognitive inventory questionnaires. The research subjects were 15 students of class XI-MIPA 6 SMAS Al Islam Krian. The student worksheets produced are very valid, with the average content and construct validation results being 87-88%. The practicality of worksheets gets a percentage > 81%, which is a very practical category. The effectiveness of worksheets is obtained based on the N-Gain score of pre-test and post-test gets moderate and high results. Thus, conclude that the blended learning-oriented worksheets are very valid, very practical, and effective. Keywords: students’ worksheet, blended learning, metacognitive skills, rate of reaction. DOI: http://dx.doi.org/10.23960/jpmipa/v23i1.pp185-197